2012
DOI: 10.1039/c2cc36219h
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed diastereoselective [2+2+2]-cycloaddition of 1,7-enynes with carbonyl compounds

Abstract: We report a gold-catalyzed [2+2+2]-cycloaddition of 1,7-enynes with carbonyl species; our experimental data suggest that the resulting oxacyclic cycloadducts arose from an interception of gold-containing cyclobutenium intermediates with carbonyl species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Again aldehydes were employed as source of carbonyl function to induce transformation of formal [2+2] adduct ( 171 ) into an oxenium cation ( 172 ), followed by cyclization and deauration leading to the tricyclic benzopyran ( 173 ) in moderate to good yield (Figure ). As complex tricyclic benzopyrans embody numerous natural product structures, the gold catalyzed enyne cycloisomerization offered a facile access to this class of molecules …”
Section: Synthesis Of Bio‐relevant Small To Medium Ring‐heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Again aldehydes were employed as source of carbonyl function to induce transformation of formal [2+2] adduct ( 171 ) into an oxenium cation ( 172 ), followed by cyclization and deauration leading to the tricyclic benzopyran ( 173 ) in moderate to good yield (Figure ). As complex tricyclic benzopyrans embody numerous natural product structures, the gold catalyzed enyne cycloisomerization offered a facile access to this class of molecules …”
Section: Synthesis Of Bio‐relevant Small To Medium Ring‐heterocyclesmentioning
confidence: 99%
“…As complex tricyclic benzopyrans embody numerous natural product structures, [61] the gold catalyzed enyne cycloisomerization offered a facile access to this class of molecules. [62] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 In another very interesting application, cyclopropenone 175 reacted with the intermediary gold carbenes 176 formed from enyne 174 and led to generate an oxenium gold intermediate 177 that formed a highly stained tricyclic intermediate 178. A cascade reaction sequence of Prins reaction, ring expansion, and hydrolysis of the resulting oxocarbenium ion (179) built up the spirocycle 180 [63] which is a fragment reminiscent of ligulactone A, B, and diaporthichalasin natural products (...…”
Section: Utilizing Carbonyl Group As a Nucleophilementioning
confidence: 99%
“…[98] 1,7-Enynes also undergo [2 + 2 + 2] cycloadditions with carbonyl compounds to give analogous products. [99] Whereas terminal alkynes react with oxoalkynes by a similar mechanism to form bicyclic compounds, [100] 1,nenynes react intermolecularly with carbonyl compounds to favor formation of fragmentation products. [101,102,103] The intramolecular [2 + 2 + 2] cycloaddition of keto enynes 48 appeared to be ideally suited for its application in the synthesis of natural products such as (+)-orientalol F (58), pubinernoid B (59), [104] and (À)-englerins A (60 a) and B (61 b) [105] (Figure 2).…”
Section: Approach Towards the Synthesis Of Arenes Via [4 + 2] Cycloadmentioning
confidence: 99%
“…[93] In particular, [2+ +2+ +2] cycloadditions of 1,7-enynes with carbonyl speciesr esulted in the formationo fo xacyclic cycloadducts from an interception of gold-containing cyclobutenium intermediates with carbonyl species (Scheme 53). [94] Another intermolecular gold(I)-catalyzed reactiono ft erminal alkynes with ketones containing ar emote alkene led to 8-oxabicyclo[3.2.1]oct-3-enes by a[ 2 + +2+ +2] cycloaddition process catalyzed by ac ationic gold complex. This experimentala nd theoretical mechanistic study indicated that gold(I)a nd aB r ønsted acid compete for the activation of the alkyne and the oxoalkene (Scheme54).…”
Section: Gold Catalysismentioning
confidence: 99%